2020
DOI: 10.1096/fj.202000166rr
|View full text |Cite
|
Sign up to set email alerts
|

Lung adenocarcinoma‐related TNF‐α‐dependent inflammation upregulates MHC‐II on alveolar type II cells through CXCR‐2 to contribute to Treg expansion

Abstract: MHC‐II on alveolar type‐II (AT‐II) cells is associated with immune tolerance in an inflammatory microenvironment. Recently, we found TNF‐α upregulated MHC‐II in AT‐II in vitro. In this study, we explored whether TNF‐α‐mediated inflammation upregulates MHC‐II on AT‐II cells to trigger Treg expansion in inflammation‐driven lung adenocarcinoma (IDLA). Using urethane‐induced mice IDLA model, we found that IDLA cells mainly arise from AT‐II cells, which are the major source of MHC‐II. Blocking urethane‐induced infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 63 publications
(179 reference statements)
1
31
0
Order By: Relevance
“…Because AT-II cells' primary function is not antigen presentation, they lack co-stimulatory signals (CD80/CD86), essential to effectively prime CD4 + T cells. Thus, instead of creating an antitumor immune response, increased AT-II cell-specific MHC-II expression can trigger Treg differentiation [104]. Numerous studies evaluated TNFR2 as a potential biomarker for NSCLC as it has been shown to be crucial for TNFα-mediated immunosuppression [105,106].…”
Section: Specificities Of Tnfα In Lung Cancer Progressionmentioning
confidence: 99%
“…Because AT-II cells' primary function is not antigen presentation, they lack co-stimulatory signals (CD80/CD86), essential to effectively prime CD4 + T cells. Thus, instead of creating an antitumor immune response, increased AT-II cell-specific MHC-II expression can trigger Treg differentiation [104]. Numerous studies evaluated TNFR2 as a potential biomarker for NSCLC as it has been shown to be crucial for TNFα-mediated immunosuppression [105,106].…”
Section: Specificities Of Tnfα In Lung Cancer Progressionmentioning
confidence: 99%
“…The tissues or cells were harvested and homogenized in 50 μl lysis buffer (50 mM Tris–HCl pH 7.5, 150 mM NaCl, 2 mM EDTA, 1% TritonX‐100, cocktail). The protocol was according to our previous experiments 2,3 …”
Section: Methodsmentioning
confidence: 99%
“…28 TNF-α is an important regulator of the tumor inflammatory microenvironment, driving lung adenocarcinoma. [2][3][4] Our recent study showed that urethane induced inflammation-driven lung adenocarcinoma (IDLA) in mice, which is dependent on TNF-αinflammatory pathway. 2,3 Therefore, it is necessary to explore how lung inflammation depends TNF-α to reprogram macrophages upregulating PD-L1 at pro-tumor stage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Macrophage receptor with collagenous structure (MARCO) expressed on the surface of tumor-associated macrophages (TAM) has been reported to promote the proliferation of Tregs and the inhibitory cytokine IL-10 secretion in NSCLC [68]. Besides, at the protumor inflammatory stage of lung cancer, TGF-α stimulation can upregulate MHC-II molecules on the surface of alveolar type II cells to trigger Treg expansion and promote the tumorigenesis of inflammation-driven lung adenocarcinoma [69].…”
Section: 3mentioning
confidence: 99%